Emerging role of cellular senescence in the pathogenesis of oral submucous fibrosis and its malignant transformation. Issue 10 (6th July 2021) - Sharma, Mohit; Hunter, Keith D.; Fonseca, Felipe Paiva; Radhakrishnan, Raghu
Abstract: Senescence is a common denominator in wound healing, fibrosis, and cancer. Although, senescence is transiently antifibrotic, when prolonged, promotes fibrosis and malignant transformation. Eligible studies indexed in MEDLINE, Embase and Web of Science were searched to understand the role of cellular senescence in the pathogenesis of oral submucous fibrosis (OSF) and its malignant transformation. The senescence‐associated secretory phenotype (SASP) components like IL‐1, IL‐6, and GRO‐α induce double‐strand DNA breaks in keratinocytes and drive genetic instability. SASP derived from myofibroblasts induces epithelial–mesenchymal transition in OSF and facilitates cancer progression. The use of senolytics has been shown to eliminate senescent cells from the areas of fibrosis, thereby preventing malignancy. Naturally occurring agents such as apigenin and kaempferol inhibit SASP. Mechanistic insight into the emerging role of senescence in the pathogenesis of OSF and modalities to inhibit senescence‐associated antiapoptotic pathways as a supplementary therapy to prevent malignant transformation of OSF is underlined.